Land assets, urban investment bonds, and local governments’ debt risk, China - Zhang, Juanfeng; Li, Lele; Yu, Ting; Gu, Jie; Wen, Haizhen (International Journal of Strategic Property Management, 2021)
As the collateral for the issuance of urban investment bonds (UIBs), land leasing revenue is the fund that is used to repay the debt with large-scale land hoarding and increasing land price due to China’s rapid urbanization. This paper employs the fixed effect model and panel data from 2006 to 2015 to analyze the influence of land hoarding and price on debt scale and risk of local governments. Results reveal that both land hoarding scale and land price exhibit a positive influence on the UIBs’ scale and risk. However, regional differences are evident. In the Eastern region, the correlation between land asset and UIBs can be testified. First published online 19 November 2020